Holistic Approach in the Development of a Rural Telecenter (Lessons Learnt from eBario Project) - Al-Khalid, Hj Othman; Johari, Abdullah; Alvin Wee, Yeo; Mohamad Nazri, Khairuddin; Khairuddin, Abdul Hamid (2007)
The development of a rural ICT project involves three main components which are the technology (hardware, software, network communication), power requirement (hydro, solar), and also the social requirement and impact. However, not many rural ICT projects take into consideration these three aspects in the implementation of the project. This paper describes a holistic approach (taking into consideration the three aspects above) in planning and implementing rural ICT project in Bario (a remote area in Sarawak, Malaysia). This project is an extension of the ongoing eBario Rural ICT project to bridge the digital divide in rural areas. This paper will describe the planning and implementation steps, challenges in the project, lessons learned from the implementation, and, community acceptance in using the system.